Eliokarmos humanii (Hyacinthaceae, Ornithogaloideae), a new species from Namaqualand in South Africa and a new combination in the genus - Martínez-Azorín, Mario; Crespo, Manuel B.; Alonso-Vargas, María Ángeles; Pinter, Michael (Phytotaxa, 2020)
A new species of the southern Africa endemic genus Eliokarmos, that includes the well-known chincherinchees, is described from the vicinity of Kotzesrus, Northern Cape Province of South Africa. Eliokarmos humanii sp. nov. is unique in the genus based on its single, slightly fleshy, suborbicular, convex leaf with ciliate margin, and the short subspiciform inflorescence with almost sessile flowers. A complete description is presented for this species, and data on morphology, ecology, and distribution are reported. In addition, Ornithogalum richtersveldensis, recently described from northwestern South Africa, is transferred to Eliokarmos based on its morphology and biogeography, and a new combination is presented for this species in the latter genus.